2013
DOI: 10.3906/sag-1205-11
|View full text |Cite
|
Sign up to set email alerts
|

JAK2 V617F Mutation in Iranian Patients with Myeloproliferative Neoplasms: Clinical and Laboratory Findings

Abstract: The JAK2 V617F mutation has been described as a frequent genetic event among a majority of patients with polycythemia vera, essential thrombocythemia, and myelofibrosis. In this research, we evaluated the prevalence of the JAK2 mutation and its clinical and laboratory correlation in patients with myeloproliferative neoplasms. Materials and methods:A total of 615 patients with suspected myeloproliferative neoplasms (MPNs) were analyzed for the JAK2 V617F mutation. After DNA extraction, detection of the mutation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 31 publications
(44 reference statements)
1
12
0
Order By: Relevance
“…This result is consistent with previous studies such as that of Poopak et al [25], which showed a higher WBC and neutrophil; Ha et al [26], which indicated a higher WBC, hematocrit, hemoglobin, neutrophil; Campbell et al [13], which showed a higher WBC, neutrophil, hemoglobin; Karkucak et al [2], which presented a higher WBC and hemoglobin; Finazzi et al [5], which showed a higher WBC, hematocrit, hemoglobin; Patriarca et al [24], which showed a higher WBC, hematocrit in patients with ET. The positive correlation with WBC and RBC counts suggest that JAK2 V617F mutation may play a role in the granulocyte production as previously reported [27].…”
Section: Discussionsupporting
confidence: 95%
“…This result is consistent with previous studies such as that of Poopak et al [25], which showed a higher WBC and neutrophil; Ha et al [26], which indicated a higher WBC, hematocrit, hemoglobin, neutrophil; Campbell et al [13], which showed a higher WBC, neutrophil, hemoglobin; Karkucak et al [2], which presented a higher WBC and hemoglobin; Finazzi et al [5], which showed a higher WBC, hematocrit, hemoglobin; Patriarca et al [24], which showed a higher WBC, hematocrit in patients with ET. The positive correlation with WBC and RBC counts suggest that JAK2 V617F mutation may play a role in the granulocyte production as previously reported [27].…”
Section: Discussionsupporting
confidence: 95%
“…In this study, we found that MPN JAK2 V617Fpositive patients had significantly higher hemoglobin levels and hematocrit which corroborates the results of previous reports. 18,20,21 Inversely, in our PV and PMF subgroups, the JAK2 V617F mutation did not influence either hemoglobin levels, or hematocrit, or leukocytes, and platelets count. These results agree with those of the Iranian 20 and Indian 21 studies.…”
Section: Discussionmentioning
confidence: 55%
“…12 Inversely, recent studies performed in patients diagnosed with the updated criteria have reported higher frequencies of the JAK2 V617F mutation in MPN patients. 16,[18][19][20][21] In fact, the frequency of the JAK2 V617F mutation in PV was 100% in Lebanese 19 and Iranian, 20 87.2% in Portuguese, 16 82% in Indian, 21 and 81% in Egyptian 18 populations. For the ET patients, the prevalence of the mutant allele was 73.4% in Portuguese, 16 70% in Indian, 21 68.29% in Lebanese, 19 50% in Egyptian, 18 and 45.66% in Iranian 20 studies.…”
Section: Discussionmentioning
confidence: 99%
“… 1 To a lower extent, this mutation has also been reported in other malignancies, including acute myeloid leukemia (AML), acute lymphoblastic leukemia (ALL), chronic myeloid leukemia (CML), chronic lymphoblastic leukemia (CLL), and some patients with MDS. 3-5 Recently, there have been cases of JAK2 V617F mutation in some leukemic patients without a history of JAK2 V617F positive MPNs. 106 , 107 The results of these studies suggest that this mutation is not specific to JAK2 V617F positive MPNs and that it may also be seen in normal individuals and underlie malignancies.…”
Section: Markers’ Expression During Leukemic Transformation In Jakmentioning
confidence: 99%
“…2 In addition, JAK2 V617F mutation has been reported in a number of other malignancies such as myeloid leukemias and has been rarely observed in lymphoid leukemias. 3-5 Since MPNs are hematopoietic stem cell (HSC) derived disorders, JAK2 V617F mutation can involve any myeloid progenitor, including granulocyte, erythrocyte, platelet, and monocyte. 6 , 7 In addition, since JAK2 is the signaling pathway of several hematopoietic factors and cytokines, the increased activity of this pathway under the influence of JAK2 V617F mutation can increase the sensitivity of multipotent progenitor cells to hematopoietic factors such as erythropoietin (EPO), thrombopoietin (TPO), and many other cytokines.…”
Section: Introductionmentioning
confidence: 99%